Life Experience of Sexual Harassment on Online Social Media and Prevention Guideline: Qualitative Mixed Method Designs - Boonthong, Nattapon; Supparekchaisakul, Numchai; Junprasert, Thasuk (The Periodical of Behavioral Science, 2023)
The qualitative mixed method designs research aims are as follows: (1) to narrate the life experience of sexual harassment on online social media from six sexual harassers experience by transcendental phenomenology based on the four steps of research process developed by Clark Moustakas. The study found that the meaning and essence of the life experience of sexual harassment on online social media are an experience that the harasser feels safe to sexual harassment. The harasser allows emotion over reasoning and reification of victims and lack of sympathy without thinking about the consequences. The harasser selection victim by know information about and the identity of victim. The victims are emotionally involved in a positive or negative relationship with their harasser, such as being intimate, offensive, irritated or angry. The harasser is self-centered and the harassment serves their own needs. The harasser lacks conscience when they harass their victim whether or not the harassment will affect the victim. The researcher used the results to answer research objectives: (2) to create prevention guidelines for sexual harassment on online social media from seven sexual harassment specialists by thematic analysis. The research results lead to presenting the sexual harassment prevention guidelines: public relations for modus operandi; enforcing the law; creating awareness of the possibility of being prosecuted; and cultivating morals and ethics.